1970
DOI: 10.1128/jvi.5.3.388-397.1970
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Transmission and In Vivo Replication of Marek's Disease Virus

Abstract: Marek's disease virus recovered from the feather follicle of infected chickens was found to be infectious for chickens in cell-free preparations. The virus replicated in epithelial cells of the germinative layer of the feather follicle epidermis, producing both intranuclear and round or diffuse cytoplasmic inclusion bodies in the infected cells. It was found at this site 2 weeks postinoculation and prior to the development of tumor or other gross lesions. In the nucleus, many naked and a few enveloped herpesvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

1971
1971
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…The localization of the MDHV antigen in chickens infected with JM isolate of MD by immunofluorescence as reported by Calnek and Hitchner (1969) and the electron microscopic studies of occurrence of virus particles in the epithelial cells of kidney and feather follicles of infected chickens (Schidlovsky et al, 1969;Nazerian and Witter, 1970) encouraged us to undertake this study. The present series of experiments showed that large quantities of MDHV antigens can be extracted from feather follicles of GA-infected chickens.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The localization of the MDHV antigen in chickens infected with JM isolate of MD by immunofluorescence as reported by Calnek and Hitchner (1969) and the electron microscopic studies of occurrence of virus particles in the epithelial cells of kidney and feather follicles of infected chickens (Schidlovsky et al, 1969;Nazerian and Witter, 1970) encouraged us to undertake this study. The present series of experiments showed that large quantities of MDHV antigens can be extracted from feather follicles of GA-infected chickens.…”
Section: Discussionmentioning
confidence: 84%
“…These studies indicate that the antigens to which infected chickens respond do not reside in the tumor cells but rather in the non-lymphoid, non-tumorous epithelial cells. Support for this also comes from various studies where, although abundant MDHV was demonstrated by electron microscopy in the epithelial cells growing in vitro (Epstein et al, 1968;Ahmed and Schidlovsky, 1968;Eidson et al, 1969) and in vivo (Nazerian and Witter, 1970) the virus could not be detected in the infiltrating lymphoid tumor cells of chickens with MD. Recently, Calnek et al (1970) reported the isolation of infectious enveloped MDHV from the feather follicle epithelium of JM-virus infected chickens; but they were unable to extract the infectious virus from the tumor cells.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Although detailed studies of virus development and morphogenesis in infected cells have been reported in herpes-type viruses (e.g., 1,7,19,24,[26][27][28], to our knowledge the kinetic events involved in MDHV infection have not been reported. There is, however, a substantial literature dealing with the biological, morphological, and immunological characteristics of MDHV (e.g., 2,3,4,6,15,17,33). This paper is an attempt to describe the levels of infectivity and antigenicity during the infectious cycle as well as the morphogenesis of the virus in infected cells.…”
mentioning
confidence: 99%